UXUC - User experience & urban creativity scientific journal, vol.3, nº1 (2021) - Rafael, Sónia (2022)
The Special Issue ‘Research through Interaction Design (RtD + IxD = RtIxD)’ emerged from our desire, as interaction design teachers, to value design as a creative, practice-led project activity, based on holistic methodology that contemplates various sides of interactive experiences. Also, as researchers, to position design methods as a noteworthy way to achieve more knowledge in an area still defining itself.